Evaluation Of Fungicides And Bioagents Against Rhizoctonia Bataticola Causing Dry Root Rot Of Chickpea (Journal of Plant Disease Sciences, 2020)
Effect of different systemic, contact and combi-fungicides and different bio agents on Rhizoctonia bataticola causing dry root of chickpea crop were studied during 2018-19 at VNMKV, Parbhani. In present studies all of the 12 fungicides tested were found effective against R. bataticola and systemic fungicides carbendazim 50% WP, tebuconazole 29.9% EC, hexaconazole 5% EC and azoxystrobin and the contact and combi-fungicides carbendazim 12% +Mancozeb 63 % WP and carboxin 37.5% + thiram 37.5% WP gave cent per cent (100%) mycelial inhibition. With regard to bio-agents, Trichoderma asperellum recorded highest mycelial growth inhibition (88.27%) followed by T. harzianum (83.4%) against Rhizoctonia bataticola.
Keywords: Chickpea; Fungicides; FungicidesDry Root Rots